PENINGKATAN KADAR PARTIKEL (TSP) DAN KEBISINGAN DARI TRANSPORTASI MATERIAL BAHAN BANGUNAN: (Studi Kasus: Pembagunan Bendungan Posi, Kabupaten Kepulauan Selayar, Provinsi Sulawesi Selatan) - -, Jumadil; Fikruddin, Muhammad (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2020)
The construction of the Posi Dam has an impact on air pollution. This study aims to determine the impact of dam construction on decreasing air quality and increasing noise due to material transportation activities. This research was conducted in the Selayar Archipelago District of South Sulawesi Province and sample testing for air quality and noise data was conducted at the Center for Occupational Safety and Health Development (BBPK3) Makassar. Forecasting methods used are mathematical calculations (modeling), expert judgment (professional judgment) and other methods carried out scientifically (scenarios, analogies and literature studies of similar activities) then converted to Environmental Quality Scale (SKL). The intended environmental quality scales are grouped in 5 categories: very good (scale 5), good (scale 4), moderate (scale 3), bad (scale 2), and very bad (scale 1) categories. The results of the study showed that the construction of the Posi Dam from the transport of building materials caused an increase in the particle content (TSP) in the air reaching 5.62 µg.m3 and noise ranged from 90 dB (A) - 100 dB (A) or an average of about 95 dB (A) the value of the parameter exceeds the quality standard based on Governor Regulation No. 69 of 2010, concerning Quality Standards and Criteria for Environmental Damage.